Effect of Gene-Based Warfarin Dosing on Anticoagulation Control and Clinical Events in a Real-World Setting - Zhang, Jinhua; Wu, Tingting; Chen, Wenjun; Fu, Jinglan; Xia, Xiaotong; Chen, Liangwan (Frontiers in Pharmacology, 2020)
Abstract: The cytochrome P450 2C9 and vitamin K epoxide reductase complex subunit 1 genotypes are associated with anticoagulation control and the clinical events of warfarin therapy. However, the clinical utility of gene-based warfarin dosing (GBWD) is controversial. We compared the anticoagulation control and clinical events related to warfarin between GBWD and clinically fixed dosing (CFD). A retrospective cohort study was conducted in a real-world setting. Of the 915 patients who were reviewed, 844 patients met the study-entry criteria; 413 cases were guided by GBWD using the International Warfarin Pharmacogenetic Consortium algorithm; 431 cases were guided by CFD (2.5 mg/day). The primary outcomes were the time needed to achieve the therapeutic International Normalized Ratio (INR) and the time in the therapeutic range (TTR) during 3 months. The time needed to achieve the therapeutic INR (in days) for patients in the GBWD group was shorter than that for patients in the CFD group (10.21 ± 4.68 vs. 14.31 ± 8.26, P < 0.001). The overall TTR (Day 4-90) was significantly different between the GBWD group and CFD group (56.86 ±10.72 vs. 52.87 ± 13.92, P = 0.007).In subgroup analysis,The TTR was also significantly different between the GBWD group and CFD group during the first month of treatment (Day 4-14：54.28 ± 21.90 vs. 47.01 ± 26.25, P = 0.012; Day 15-28: 59.60 ± 20.12 vs. 51.71 ± 18.96, P = 0.001). However, no significant difference in the TTR was observed after 29 days of treatment. These data suggest that GBWD provided clinical benefits.